Aortic Valve Replacement: Treatment by Sternotomy versus Minimally Invasive Approach - Ferreira,Renata Tosoni Rodrigues (2016)
Abstract Objective: To compare the results of aortic valve replacement with access by sternotomy or minimally invasive approach. Methods: Retrospective analysis of medical records of 37 patients undergoing aortic valve replacement by sternotomy or minimally invasive approach, with emphasis on the comparison of time of cardiopulmonary bypass and aortic clamping, volume of surgical bleeding, time of mechanical ventilation, need for blood transfusion, incidence of atrial fibrillation, length of stay in intensive care unit, time of hospital discharge, short-term mortality and presence of surgical wound infection. Results: Sternotomy was used in 22 patients and minimally invasive surgery in 15 patients. The minimally invasive approach had significantly higher time values of cardiopulmonary bypass (114.3±23.9 versus 86.7±19.8min.; P=0.003), aortic clamping (87.4±19.2 versus 61.4±12.9 min.; P<0.001) and mechanical ventilation (287.3±138.9 versus 153.9±118.6 min.; P=0.003). No difference was found in outcomes surgical bleeding volume, need for blood transfusion, incidence of atrial fibrillation, length of stay in intensive care unit and time of hospital discharge. No cases of short-term mortality or surgical wound infection were documented. Conclusion: The less invasive approach presented with longer times of cardiopulmonary bypass, aortic clamping and mechanical ventilation than sternotomy, however without prejudice to the length of stay in intensive care unit, time of hospital discharge and morbidity.